LRP1 Modulates APP Intraneuronal Transport and Processing in Its Monomeric and Dimeric State - Herr, Uta-Mareike; Strecker, Paul; Storck, Steffen E.; Thomas, Carolin; Rabiej, Verena; Junker, Anne; Schilling, Sandra; Schmidt, Nadine; Dowds, C. Marie; Eggert, Simone; Pietrzik, Claus U.; Kins, Stefan (Frontiers in Molecular Neuroscience, 2017)
The low-density lipoprotein receptor-related protein 1, LRP1, interacts with APP and affects its processing. This is assumed to be mostly caused by the impact of LRP1 on APP endocytosis. More recently, also an interaction of APP and LRP1 early in the secretory pathway was reported whereat retention of LRP1 in the ER leads to decreased APP cell surface levels and in turn, to reduced Aβ secretion. Here, we extended the biochemical and immunocytochemical analyses by showing via live cell imaging analyses in primary neurons that LRP1 and APP are transported only partly in common (one third) but to a higher degree in distinct fast axonal transport vesicles. Interestingly, co-expression of LRP1 and APP caused a change of APP transport velocities, indicating that LRP1 recruits APP to a specific type of fast axonal transport vesicles. In contrast lowered levels of LRP1 facilitated APP transport. We further show that monomeric and dimeric APP exhibit similar transport characteristics and that both are affected by LRP1 in a similar way, by slowing down APP anterograde transport and increasing its endocytosis rate. In line with this, a knockout of LRP1 in CHO cells and in primary neurons caused an increase of monomeric and dimeric APP surface localization and in turn accelerated shedding by meprin β and ADAM10. Notably, a choroid plexus specific LRP1 knockout caused a much higher secretion of sAPP dimers into the cerebrospinal fluid compared to sAPP monomers. Together, our data show that LRP1 functions as a sorting receptor for APP, regulating its cell surface localization and thereby its processing by ADAM10 and meprin β, with the latter exhibiting a preference for APP in its dimeric state.